Personality-centered education as a resource of health protection of future border guard officers - Пантєлєєв, Кирило (Pedagogy of Higher and Secondary Education, 2014)
Panteleev K. V. Personality-centered education as a resource of health protection of future border guard officers. The article studies the issues with regard to developing person’s needs and abilities for self-development in a training process in context of health protection.